Internalisasi Nilai-Nilai Islam Wasathiyah dalam Modul Pengantar Studi Islam Universitas Terbuka: Studi Kasus pada Mahasiswa Pendidikan Agama Islam - Sariyani, Sariyani (PAI RAFAH, 2025)
This study explores the internalization of wasathiyah (Islamic moderation) values within the Introduction to Islamic Studies (PSI) module at Universitas Terbuka and its influence on character development among Islamic Education (PAI) students. Using a qualitative case study design, data were collected from 50 students, three lecturers, and three experts through interviews, observation, and document analysis. The data were analyzed using the Miles and Huberman model, covering data reduction, presentation, and verification. The findings show that wasathiyah values such as ‘adl (justice), tawazun (balance), and tasamuh (tolerance) are integrated thematically within the PSI module. However, their internalization is often limited by descriptive learning methods that lack reflective and dialogic engagement. Lecturers play a crucial role as facilitators in promoting active moral reflection through contextual and case-based approaches. This study highlights the need for a transformative learning design that bridges cognitive knowledge with moral practice, enabling students to embody moderation values in real-life contexts. The novelty of this study lies in identifying pedagogical gaps in distance Islamic education and proposing reflective, value-based strategies to strengthen wasathiyah-oriented character formation among future Muslim educators.